2005
DOI: 10.1097/01.ccm.0000153416.41398.a9
|View full text |Cite
|
Sign up to set email alerts
|

Adrenomedullin and its binding protein attenuate the proinflammatory response after hemorrhage

Abstract: The combined administration of AM and AMBP-1 effectively suppresses hemorrhage-elicited organ injury and reduces hemorrhage-induced mortality, partly through down-regulation of proinflammatory cytokines (tumor necrosis factor and high mobility group box 1) and up-regulation of the anti-inflammatory cytokine interleukin-10.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 52 publications
2
36
0
Order By: Relevance
“…An increasing number of agents (ethyl pyruvate, stearoyl lysophosphatidylcholine, nicotine) dose-dependently inhibits HMGB1 release, and confers significant protection against lethal sepsis [2,8,[35][36][37][38]. Neutralizing antibodies against IFN-γ, a cytokine capable of stimulating HMGB1 release [10], significantly reduced circulating HMGB1 levels in septic rats, and consequently rescued rats from lethal sepsis [39].…”
Section: Suppression Of Hmgb1 Release -The Caging Of the Beastmentioning
confidence: 99%
“…An increasing number of agents (ethyl pyruvate, stearoyl lysophosphatidylcholine, nicotine) dose-dependently inhibits HMGB1 release, and confers significant protection against lethal sepsis [2,8,[35][36][37][38]. Neutralizing antibodies against IFN-γ, a cytokine capable of stimulating HMGB1 release [10], significantly reduced circulating HMGB1 levels in septic rats, and consequently rescued rats from lethal sepsis [39].…”
Section: Suppression Of Hmgb1 Release -The Caging Of the Beastmentioning
confidence: 99%
“…The band densities were determined using a BioRad image system. Our previous study indicates that the anti-human AMBP-1 antibodies recognize rat AMBP-1 (27). The band densities were determined with the use of a Bio-Rad image system.…”
Section: Western Blot Analysis Of Ambp-1mentioning
confidence: 99%
“…Interestingly, the activity of AM-BP as complement factor-H (responsible cofactor for the factor I-dependant cleaving of complement C3B) is increased when AM is bound [17] suggesting that aspects of the innate complement cascade within the mammary gland [49] are also modulated by AM. Furthermore, increased beneficial clinical outcome (decreased morbidity and mortality) recently has been attributed to the use of an AM/AM-BP complex as an intervention strategy to limit the complicating effects of sepsis and hypovolumic shock on progression into multiple organ failure [19,[42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…Further research into this binding protein revealed it to be a member of the complement cascade, namely, complement factor-H (C-F H , [17]). The interaction of AM with AM-BP/C-F H results in the modulation of the bioactivity of each component of the complex [17][18][19].…”
Section: Introductionmentioning
confidence: 99%